News and Sovereign Default Risk in Small Open Economies - C. Bora Durdu; Ricardo Nunes; Horacio Sapriza (Koç University-TÜSİAD Economic Research Forum (ERF), 2013)
This paper builds a model of sovereign debt in which default risk, interest rates, and debt depend not only on current fundamentals but also on news about future fundamentals. News shocks affect equilibrium outcomes because they contain information about the likelihood that the government repays its debt in the future. First, in the model with news shocks not all defaults occur in bad times, bringing the model closer to the data. Second, the news shocks help account for key differences between developing and more developed economies: as the precision of news improves, the model predicts lower variability of consumption, less countercyclical trade balance and interest rate spreads, as well as a higher level of debt more in line with the characteristics of more developed economies. Third, the model also captures the hump-shaped relationship between default rates and the precision of news obtained from the data. Finally, the news shocks have a nonmonotonic effect on the welfare.
Keywords: F34; F41; 330; sovereign default risk; news shocks; endogenous borrowing constraints; Länderrisiko; Wirtschaftsindikator; Informationswert; Informationsverbreitung; Schock; Kleine offene Volkswirtschaft; Theorie